Cell-specific expression of aquaporin-5 (Aqp5) in alveolar epithelium is directed by GATA6/Sp1 via histone acetylation - Per Flodby (Nature Portfolio, 2017)
Abstract Epigenetic regulation of differentiation-related genes is poorly understood. We previously reported that transcription factors GATA6 and Sp1 interact with and activate the rat proximal 358-bp promoter/enhancer (p358P/E) of lung alveolar epithelial type I (AT1) cell-specific gene aquaporin-5 (Aqp5). In this study, we found that histone deacetylase (HDAC) inhibitor suberoylanilide hydroxamic acid (SAHA) increased AQP5 expression and Sp1-mediated transcription of p358P/E. HDAC3 overexpression inhibited Sp1-mediated Aqp5 activation, while HDAC3 knockdown augmented AQP5 protein expression. Knockdown of GATA6 or transcriptional co-activator/histone acetyltransferase p300 decreased AQP5 expression, while p300 overexpression enhanced p358P/E activation by GATA6 and Sp1. GATA6 overexpression, SAHA treatment or HDAC3 knockdown increased histone H3 (H3) but not histone H4 (H4) acetylation within the homologous p358P/E region of mouse Aqp5. HDAC3 binds to Sp1 and HDAC3 knockdown increased interaction of GATA6/Sp1, GATA6/p300 and Sp1/p300. These results indicate that GATA6 and HDAC3 control Aqp5 transcription via modulation of H3 acetylation/deacetylation, respectively, through competition for binding to Sp1, and suggest that p300 modulates acetylation and/or interacts with GATA6/Sp1 to regulate Aqp5 transcription. Cooperative interactions among transcription factors and histone modifications regulate Aqp5 expression during alveolar epithelial cell transdifferentiation, suggesting that HDAC inhibitors may enhance repair by promoting acquisition of AT1 cell phenotype.